Swakiddo watch / Mohamad Ariff Mohamad Noh and Mohamad Amir Hakim Ishak - Mohamad Noh, Mohamad Ariff; Hakim Ishak, Mohamad Amir (2018)
Losing our phone surely can make us restless. Same goes to lose bike or car. But what if we lose our children? Not just can make us feel restless but it can make us feel like losing our minds. Based on statistic made by Polis Di Raja Malaysia (PDRM), there is 723 cases regarding the lost child they received since January to June, 2017. While 345 cases have been successfully settled, the remaining are still can't be founded. The reasons why this issues happened is firstly, because the abduction crime is common in our country these days and thus the safety of our children in on stake. Next, because of the lack of attention given by parents to their children either in shopping mall or recreation park and even in their houses. Lastly, kids love adventure, they always do it everywhere no matter in shopping mall, mosque and even their own house. Worst case scenario, there might be their adventure ended with lost without track.